The effect of cannabidiol on seizure features and quality of life in drug-resistant frontal lobe epilepsy patients: a triple-blind controlled trial - Ebadi, Seyyed Reza; Saleki, Kiarash; Adl Parvar, Tanin; Rahimi, Negin; Aghamollaii, Vajiheh; Ranji, Sara; Tafakhori, Abbas (Frontiers in Neurology, 2023)
Background: Treatment resistant epileptic seizures are associated with reduced quality of life (QoL). As polypharmacy with routine antiseizure medications has many side effects, novel add-on treatments are necessary. Recent research showed efficacy of add-on therapy by Cannabidiol (CBD) on refractory epilepsy. We attempted to extend data on efficacy and safety profile of CBD in patients with frontal lobe treatment-resistant epilepsy. Methods: 27 patients were recruited into two CBD (n = 12) and placebo (n = 15) groups. CBD group received a highly-purified liposomal preparation of the drug in addition to routine antiseizure medications. The placebo group only received antiseizure medications. This experiment followed a triple-blinding protocol. Outcome measures were seizure frequency, Chalfont seizure severity scale (CSSS), and quality of life questionnaire score (QOLIE-31) assessed at baseline, 4-weeks, and 8-weeks. Results: At 4-weeks, results indicated higher fraction of patients in the CBD group (66.67%) showed improvement in seizure, compared to the placebo group (20.00%). before-after comparison revealed that CBD, unlike routine ADEs, was effective in reducing the occurrence of seizures at the study’s final timepoint (mean difference 45.58 95% CI [8.987 to 82.18], p = 0.009). Seizure severity was not affected by study groups or time interval (repeated-measures ANOVA p > 0.05). Post-hoc tests found QoLI-31 score was improved at 8-weeks compared to baseline (mean diff. -5.031, 95% CI [-9.729 to -0.3328], p = 0.032). The difference in cases who experienced enhanced QoL was meaningful between the CBD and placebo groups at 8-weeks (RR: 2.160, 95% CI [1.148 to 4.741], p = 0.018), but not at 4-weeks (p = 0.653). A positive finding for QoL improvement was associated with a positive finding for seizure frequency reduction (r = 0.638, 95% CI [0.296 to 0.835], p = 0.001). Interestingly, limiting the correlation analysis to cases receiving CBD indicated that QoL improvement was not linked with seizure parameters such as severity and frequency (p > 0.05). Conclusion: The present study suggests benefit of purified and highly-efficient preparation of CBD for seizure frequency reduction and improvement of QoL in refractory frontal lobe epilepsy. Further study with longer follow-ups and larger sample size is advised.